Analisis Dampak Anggaran Infrastruktur Perkapita yang Dimediasi oleh Anggaran Keamanan Perkapita Berpengaruh Terhadap Pertumbuhan Ekonomi Provinsi Aceh - Zainuddin; Hamdiah, Cut; Maryam; T. Makmur (Jurnal EMT KITA, 2024)
The aim of this research is to examine the influence of the per capita infrastructure budget and per capita security budget on economic growth as measured by Gross Regional Domestic Product in Aceh Province. As well as to examine the per capita security budget mediating the per capita infrastructure budget in influencing growth in Aceh Province during the observation period. The data in this analysis comes from www.bps.go.id and www.djpk.go.id. This analysis uses panel data analysis with a random effect model and uses the Sobel test. The research results show that the per capita infrastructure budget and per capita security budget simultaneously influence economic growth in Aceh province. The per capita infrastructure budget is partially significant to economic growth in Aceh province, and the per capita security budget is not significant to economic growth in Aceh province. Furthermore, the per capita security budget variable cannot mediate the per capita infrastructure budget in influencing economic growth in Aceh Province.